Borland C++ 3.1 object-oriented programming - Faison, Ted (Carmel, Indiana : Sams Publishing, 1992)
This book/disk package aims to offer a rapid pathway to understanding Borland C++OOP software. At the same time, it gives useful tips, includes tutorial exercises, and offers a detailed reference section. The material is relevant to Borland C++, version 2.0.
Preface -- Introduction -- Part I. Object-Oriented Programming with Borland C++ -- 1. Basics -- 2. Objects and Classes -- 3. Inheritance -- 4. Overloading -- 5. Polymorphism -- 6. Streams -- 7. The Container Class Library -- Part II. Developing Windows and DOS Applications -- 8. Classes for Windows Programming -- 9. A Complete Windows Program -- 10. Object Windows Library Clauses -- 11. OWL Applications -- 12. Turbo Vision Classes -- 13. Turbo Vision Applications -- Bibliography -- Index.
Revised edition of: Borland C++ 3 object-oriented programming. 1st ed. c1992, 1991 printing.
Includes bibliographical references and index.
Keywords: BORLAND C++